Socialization of the Church's Challenges in Facing the Influence of Globalization for the Millennial Generation at the Kalam Kudus Doyo Baru Congregation - Gainau, Maryam; Warwer, Fredrik; Garjalay, Sarce; Kafiar, Frans; Bawan, Sara Bunda Desi (Abdi Masyarakat, 2024)
Community Service Activities by STAKPN Sentani Postgraduate lecturers and educational staff at the Kalam Kudus Doyo Baru Congregation aim to equip the millennial generation to face the challenges of globalization on faith and spirituality. In the modern era filled with the flow of digital information, values such as secularism, materialism and moral relativism often conflict with Christian teachings. Through lecture methods, group discussions and Biblical training, this activity provides participants with in-depth insight into the importance of maintaining the foundations of faith amidst the negative influences of globalization. This activity also emphasizes the role of technology as a means of deepening faith and the importance of a strong spiritual community among millennials. As a result, the younger generation of the Kalam Kudus Doyo Baru Congregation is better prepared to face cultural shifts without losing their Christian identity. With creative and relevant approaches, such as the use of digital media and innovative services, it is hoped that participants will become more actively involved in church life. This service succeeded in having a significant impact in strengthening the faith and spirituality of the millennial generation, as well as strengthening their commitment to maintaining Christian values in the era of globalization.